Blood Urea Nitrogen to Creatinine ratio in Differentiation of Upper and Lower Gastrointestinal Bleedings; a Diagnostic Accuracy Study - Zia Ziabari, Seyyed Mahdi; Rimaz, Siamak; Shafaghi, Afshin; Shakiba, Maryam; Pourkazemi, Zahra; Karimzadeh, Elnaz; Amoukhteh, Melika (Archives of Academic Emergency Medicine, 2019)
Introduction: Finding easily accessible and non-invasive methods for differentiating various sources of gastrointestinal (GI) bleeding before performing endoscopy and colonoscopy is of great interest. The present study was designed with the aim of evaluating the screening performance characteristics of blood urea nitrogen (BUN) to Creatinine (Cr) ratio in this regard. Methods: The present diagnostic accuracy study was performed on patients with acute GI bleeding presenting to emergency department from 2011 to 2016, in a retrospective manner. BUN/Cr ratio was calculated for all patients and its accuracy in differentiation of upper and lower GI bleedings, confirmed via endoscopy or colonoscopy, was evaluated. Results: A total of 621 patients with the mean age of 59.49±17.94 (5 – 93) years were studied (60.5% male). Area under the receiver operating characteristic (ROC) curve of BUN/Cr ratio for predicting the source of GI bleeding was 0.63 (95% CI: 0.57 – 0.68). Sensitivity, specificity, positive and negative predictive values, and positive and negative likelihood ratios of BUN/Cr ratio at 35 cut-off point were 19.63% (95%CI: 16.69 – 23.45), 90.16% (95%CI: 83.11 – 94.88), 89.09 (95%CI: 81.35 – 93.98), 21.53 (95%CI: 18.09 – 25.39), 8.16 (95%CI:4.76 – 13.98), and 3.65 (95%CI: 3.44 – 3.87), respectively. Conclusion: Considering the relatively proper specificity and positive predictive value of BUN/Cr ratio, in cases that bleeding source cannot be determined using other non-invasive methods, values higher than 35 can predict upper GI bleeding with high probability. However, due to the low sensitivity, values less than 35 are not diagnostic.